Starbucks : driving growth through new dining occasions - Sawhney, Mohanbir (London : Kellogg School of Management, 2018)
In 2008, Starbucks was in crisis as a result of undisciplined growth and loss of focus, and its stock declined almost 70%. In August of that year, Howard Schultz, the founder of Starbucks, came out of retirement to take over as the CEO. The company regained its footing by refocusing on its core and driving strong organic growth. By 2014, the stock price had reached $40, an all-time high. To prevent history from repeating itself, Schultz wanted to ensure that Starbucks' growth strategies not only addressed market opportunities, but also were aligned with the company's brand image, assets, and capabilities.
Originally Published InSawhney, M. (2018). Starbucks: Driving growth through new dining occasions. 5--218--253. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Schultz, Howard; Starbucks Coffee Company; Business planning; Strategic planning; Branding (Marketing)